Morphological Characteristics of Graduates from Basic Professional Schools of Agriculture - Wrońska-Węcław, Wanda (Anthropological Review, 1977)
The material consists of measurements taken on graduates of Basic Professional Schools of Agriculture having a generalized training program, situated on the territory of the former Lublin voivodeship. In the spring of 1975, examinations were carried out on 222 girls at the age of 16 and 17 years and 53 boys aged 17. The control group comprised high school students of the same age (138 girls, 41 boys). The results were also checked against data for urban youths of the same age. On all examined individuals, 15 body measurements were taken; afterward, the circumference of arm muscles, percentage of fat, and lean body mass were calculated. It has been found that examined graduates, on average, do not differ from high school students. The only difference lies in that the graduates show a higher proportion of individuals with body height below the population's mean. This fact, with a high degree of probability, may be attributed to the pre-high school morphological selection of candidates for professional schools and regular high schools. Therefore, youths studying in Basic Professional Schools of Agriculture do not show retardation of physical development.